Academic Goals and Self-Handicapping Strategies in University Students. (23rd May 2016) - Ferradás, María del Mar; Freire, Carlos; Valle, Antonio; Núñez, José Carlos
Abstract: In highly competitive settings like university, the fear of failure leads some students to protect their self-worth using self-handicapping strategies. The present investigation examines to what extent academic goals are related to those tactics in university students. Specifically, MANCOVA was applied to estimate statistical differences linked to behavioral and claimed self-handicapping strategies according to the level (high/medium/low) of four types of academic goal (achievement approach, achievement avoidance, mastery approach, and work avoidance). Degree, year in school, and gender were entered as covariates. 940 students (86.5% women) from University of A Coruña ( M = 20.44; SD = 1.73) participated. Results show that: (a) both behavioral and claimed self-handicapping are promoted by ego-oriented goals (achievement avoidance, F (2, 937) = 23.56, p < .001, η p 2 = .048; achievement approach, F (2, 937) = 7.49, p < .001, η p 2 = .016); (b) work avoidance goals are related to behavioral self-handicapping ( F (2, 937) = 9.09, p < .001, η p 2 = .019), but are not statistically linked to claimed self-handicapping; and (c) mastery approach goals are significantly, negatively related to both types of self-handicapping ( F (2, 937) = 20.09, p < .001, η p 2 = .041). Psychological and educational implications of the findings are discussed.